2003
DOI: 10.4049/jimmunol.171.10.5337
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Transfer of Class I MHC Allele Specificity between Activating Ly-49P and Ly-49W Receptors by Exchange of β4–β5 Loop Residues

Abstract: Receptors of the Ly-49 multigene family regulate rodent NK cell functions. Ly-49Rs are highly polymorphic and exist in either activating or inhibitory forms. Examples of both Ly-49 receptor types have been shown to recognize class I MHC ligands. Ly-49Rs can distinguish between class I alleles, but the molecular basis of this discrimination is unknown. Two activating receptors, Ly-49P and Ly-49W, differ in class I recognition, recognizing H-2Dd, or H-2Dd and Dk, respectively. In this report, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…2 and 7), provide support for subsite C contributing to allele specificity of Ly49 interaction. Furthermore, our previous findings showed that substituting a sequence within the ␤4-␤5 loop of Ly49W for that of another Ly49 receptor, Ly49P, allows the mutant Ly49P to recognize a new MHC I allele product (43,52). Because the ␤4-␤5 loop of Ly49P and W, similar to Ly49A (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 7), provide support for subsite C contributing to allele specificity of Ly49 interaction. Furthermore, our previous findings showed that substituting a sequence within the ␤4-␤5 loop of Ly49W for that of another Ly49 receptor, Ly49P, allows the mutant Ly49P to recognize a new MHC I allele product (43,52). Because the ␤4-␤5 loop of Ly49P and W, similar to Ly49A (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Overlaid onto these primary interactions are secondary ones involving L6, which displays considerable sequence variability within each group. As demonstrated by mutational analysis (30), L6 regulates the specificity of Ly49s for particular H-2D or H-2K alleles, most likely by modifying the affinity derived from conserved interactions. However, it is not apparent which allele-specific features of MHC-I are detected by L6.…”
Section: Structure Of the Ly49c-h-2k Bmentioning
confidence: 99%
“…However, it is not apparent which allele-specific features of MHC-I are detected by L6. In the Ly49A-H-2D d structure, all MHC-I residues within 10 Å of L6 are identical between H-2D d and H-2D k , yet amino acid changes in L6 alone suffice to alter the specificity of Ly49s for these alleles (29,30). Because H-2D…”
Section: Structure Of the Ly49c-h-2k Bmentioning
confidence: 99%
“…The identity of the insert was verified by DNA sequencing. RNK-16 cells were stably transfected with the construct as previously described (21). Positive expression of Ly49Wi2 was verified by surface staining with STOK2 (anti-Ly49i2) Ab by flow cytometry.…”
Section: Generation Of Rnk-16 Effector Cells Expressing Chimeric Ly49mentioning
confidence: 99%